2019
DOI: 10.1016/j.cgh.2018.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values of Esophageal Distensibility and Distension-Induced Contractility Measured by Functional Luminal Imaging Probe Panometry

Abstract: Normal parameters of FLIP panometry are EGJ-DI greater than 2.8 mm/mm Hg, DP greater than 18 mm, and antegrade contractions that occur in a repetitive pattern (RACs)-these can be used as normal findings for esophageal distensibility and distension-induced contractility. These values can be used in comparative studies of esophageal diseases, such as achalasia and eosinophilic esophagitis, and will facilitate application of FLIP panometry to clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
163
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(173 citation statements)
references
References 17 publications
9
163
0
1
Order By: Relevance
“…For comparison, 20 healthy, asymptomatic, adult volunteers were also included. These subjects were previously described . Informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, 20 healthy, asymptomatic, adult volunteers were also included. These subjects were previously described . Informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Functional luminal imaging probe data including distension volume, intra‐balloon pressure, and 16 channels of luminal diameter were exported to a customized program as previously described . Esophageal body contractions and contractility patterns were identified similarly to previous studies . Esophageal body contractions were identified by a transient decrease of ≥5 mm in the luminal diameter in ≥3 adjacent impedance planimetry channels using FLIP topography plots and 16‐channel diameter line‐tracing output.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent prospective study conducted by Carlson et al the normative data of FLIP in 20 asymptomatic volunteers were evaluated across the EGJ and distal esophagus. The average EGJ distensibility index (DI) was greater than 2.8 mm 2 /mmHg, and distensibility plateaus were greater than 18 mm in all particiants . Therefore, normal DI parameters for the esophagus can be used to facilitate the application of FLIP in esophageal diseases in clinical practice.…”
Section: Flip For Egj Evaluationmentioning
confidence: 99%
“…The average EGJ distensibility index (DI) was greater than 2.8 mm 2 /mmHg, and distensibility plateaus were greater than 18 mm in all particiants. 8 Therefore, normal DI parameters for the esophagus can be used to facilitate the application of FLIP in esophageal diseases in clinical practice.…”
Section: Flip For Egj Evaluationmentioning
confidence: 99%
“…Acceptability of procedure, measured using visual analog scale (VAS), was significantly higher for Cytosponge (median, 6. In this study of 20 healthy volunteers, Carlson and colleagues 5 established normal values of esophageal distensibility and distension-induced contractility using FLIP. Using a 16-cm FLIP positioned across the esophagogastric junction (EGJ) and distal esophagus, they observed that all 20 asymptomatic subjects had an EGJ distensibility index > 2.8 mm 2 /mmHg, maximum EGJ diameter > 18 mm, distal esophageal body distensibility plateau > 18 mm, and exhibited a pattern of repetitive antegrade contractions in response to distension.…”
Section: Safety and Acceptability Of Esophageal Cytosponge Cell Collementioning
confidence: 99%